Evidence for benefits from treating cervical ectopy: literature review - Luís Carlos Machado Junior; Ana Sílvia Whitaker Dalmaso; Heráclito Barbosa de Carvalho (São Paulo Medical Journal)
CONTEXT AND PURPOSE: Uterine cervical ectopy (cervical erosion) is today considered to be a physiological condition, but there still seems to be a strong tendency towards treating it. The purpose of this study was to review the medical literature for evidence regarding benefits from treating cervical ectopy. METHODS: The following databases were reviewed: Medical Literature Analysis and Retrieval System Online (Medline), Excerpta Medica Database (Embase), Literatura Latino-Americana e do Caribe em Ciências da Saúde (Lilacs) and Cochrane Library databases. In addition, six medical textbooks were consulted. RESULTS: The review showed that: 1) there is probably an association between ectopy and higher risk of Chlamydia trachomatis, human papillomavirus and human immunodeficiency virus infection; 4) there is probably an association between ectopy and cervical intraepithelial neoplasia; 5) there is an association between ectopy and mucous discharge and nocturia; and 6) there is no evidence of an association between ectopy and cervical cancer, or of protection against cervical cancer associated with ectopy treatment. CONCLUSIONS: 1) No data were found in the medical literature to support routine treatment for ectopy; 2) Treatment could be recommended for symptom relief, but more symptoms are attributed to ectopy than could be demonstrated in a controlled study; 3) Further studies to test the hypothesis of protection against cervical cancer associated with treatment are necessary.